How Do Gender and Social Status Shape Adolescents' Perceptions and Attitudes Toward Online Gender-Based Violence? - Dini Rakhmawati; Venty Venty; Heri Saptadi Ismanto; Jovita Julienjatingsih (Bulletin of Counseling and Psychotherapy)
Online gender-based violence (OGBV) in Indonesia has experienced a significant increase in 2023 compared to the previous year. OGBV is a term that refers to acts of violence or sexual harassment, especially targeting women, which are carried out through internet technology. Teenagers are a generation of digital natives who are highly dependent on internet technology. Engaging in harmful content online has also been shown to pose a danger to physical and mental health. Understanding adolescents' perceptions and attitudes towards OGBV is a crucial step in efforts to overcome and prevent it. This study aims to: 1) Identify adolescents' perception of OGBV based on gender and social background; 2) Analyze adolescents' attitudes towards OGBV based on gender and social background. This quantitative survey design took the research subjects of high schools in Semarang, approximately 30882 adolescents in 16 sub-districts in Semarang with a random sampling technique using a total of 545 respondents. Because the data was not normally distributed, the data analysis used The Mann-Whitney U test and The Kruskal-Wallis H analysis. The results of the study show that women's perception is better than men's. The higher the socio-economic status, the better the perception of OGBV. Women's attitudes are higher than men's attitudes towards OGBV. There was no significant difference in OGBV's attitude based on socioeconomic status.